Fe-Mn-Al-C계 경량철강의 미세조직 및 기계적 물성 변화에 미치는 냉각속도의 영향 - 박준영; Jun Young Park; 박성준; Seong-jun Park; 이재현; Jae-hyun Lee; 문준오; Joonoh Moon; 이태호; Tae-ho Lee; 정경재; Kyeong Jae Jeong; et al. (대한금속·재료학회지, 55(12), 2017)
The effects of cooling after solution heat treatment on the microstructure and mechanical properties of light-weight steels were investigated using Fe-30Mn-xAl-0.9C alloys containing 9.0-12.8 wt% Al. Lab-scale specimens (thickness: 10 mm) of the alloys were cooled by different cooling rates from -337 to -0.053 ℃/s using water, air, and furnace cooling. As the cooling rate decreased, hardness of the alloys increased due to precipitation of κ-carbides. However, reduction of the cooling rate induced the growth of intergranular κ-carbides. This resulted in the decrease of impact absorbed energy of the alloys at room temperature, and exhibited intergranular brittle fracture behavior. The 12.8 wt% Al alloy cooled at the slowest cooling rate in particular showed the formation of β-Mn. To estimate the cooling rates of large-scale slabs of light-weight steels, finite element simulations were conducted. The cooling rates at the center of the slab under air and water cooling (free convection) were calculated to be -0.049 and -0.15 ℃/s, respectively. The results indicated that water cooling could prevent the excessive formation of κ-carbides/β-Mn during fabrication of large-scale slabs of alloys containing an Al content lower than 10.5 wt%. (Received September 1, 2017; Accepted September 20, 2017)